And put away childish things - Tchaikovsky, Adrian, 1972- (Terrible worlds, 2023)
"Harry Bodie has a famous grandmother, who wrote beloved children's books set in the delightful world of Underhill. Harry himself is a failing kids' TV presenter whose every attempt to advance his career ends in self-sabotage. His family history seems to be nothing but an impediment. An impediment... or worse. What if Underhill is real? What if it has been waiting decades for a promised child to visit? What if it isn't delightful at all? And what if its denizens have run out of patience and are taking matters into their own hands?" --